(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The 2017 Dadin Kowa flood had a more devastating effect in Hore Gare and Tunga areas. The flood occurred as a result of high rainfall, obstruction, siltation and encroachment into flood-prone areas. Monthly maximum and annual rainfall analyses were carried out. The month of June, 2017 received the maximum monthly rainfall of a total of 344 mm which coincided with the month the flood occurred. The analysis of data indicated that flooding in Dadin Kowa town is rainfall-induced and the river channels are expected to be on higher risks of flooding when the channel obstruction capacity coincides with high rainfall intensity. The mean value of annual and maximum rainfall is 834.93 mm and 249.08 mm with standard deviation of 131.95 mm and 49.24 mm respectively at Dadin Kowa town. The recurrence interval of 2, 5, 10, 25, 50, 100 and 200 years of monthly maximum rainfall is 250.70 mm, 292.80 mm, 313.00 mm, 332.70 mm, 344.30 mm, 353.90 mm and 362.00 mm respectively. The frequency analysis of the return period of the maximum monthly rainfall of 344.00 mm is expected to occur in 50 years from 2018 with a magnitude of 344.30 mm. Also, the recurrence interval of 2, 5, 10, 25, 50, 100 and 200 years of annual maximum rainfall is 838.78 mm, 949.40 mm, 1003.60 mm, 1057.70 mm, 1090.30 mm, 1118.10 mm and 1142.10 mm respectively. The frequency analysis of the return period of the